AMINOACID COMPOSITION OF SOME SPECIES FROM INULA GENUS - A. A. Kruglaya (Фармация и фармакология (Пятигорск), 2017)
The majority of medicinal plants and medicinal plant raw materials are understudied pharmacgostically. These plants include species from Inula genus, which range in Russia amounts to up to 40 species. Rhizomes and roots of the Inula helenium L. are broadly applied in scientific and traditional medicine. They have expectorate, styptic, and anti-inflammatory properties.The purpose of the study was to determine the amino-acid composition of some species from Inula genus (Inula germanica, Inula ensifolia, Inula aspera, Inula orientalis), which grow in different regions if the North Caucasus.Methods. The studies were carried out using AAA 400 amino acid analyzer, highly specialized automatized liquid chromatographer with computer management. Aboveground parts of the plants, gathered in mass blossom phase from wild-growing plants and then dried out were the objects of the study.Results. For the first time the amino acid composition and raw protein of some species from Inula genus was determined (Inula germanica, Inula ensifolia, Inula aspera, Inula orientalis), 16 amino acids were discovered, 7 of which were essential, and raw proteins which substantival composition amounted to 16.19% in Inula germanica, 10.78% in Inula ensifolia, Inula aspera (11.15%), Inula orientalis (13.94%).Conclusion. The results of the studies conducted broaden the data about amino acids and protein composition and quantitative content in the species from Inula genus and can be used to develop methods of analysis of the drugs, obtained from these plants.